Design of UV Absorbing Donor Molecules for Nearly Imperceptible Organic Solar Cells - Ball, Melissa L.; Burlingame, Quinn; Smith, Hannah L; Liu, Tianran; Parkin, Sean R.; Kahn, Antoine; Loo, Yueh-Lin (ACS Energy Letters, 2022)
Transparent photovoltaic cells are an emerging technology that can provide point-of-use electricity generation for building integrated applications. While most transparent solar cells to date target absorption of the photon-rich near-infrared portion of the solar spectrum, these devices compromise color neutrality and transparency because of parasitic absorption of long-wavelength visible light. One solution to eliminate parasitic absorption is to employ materials that absorb near-ultraviolet light with sharper absorption cutoffs. Herein, we demonstrate organic donor materials based on N,N′-diaryl-diamines that incorporate a series of aryl linkers to systematically tune their absorption profiles. When paired with acceptor 4,6-bis(3,5-di-4-pyridinylphenyl)-2-methylpyrimidine in an inverted architecture with an indium tin oxide top electrode and an organic optical outcoupling layer, the three best-performing transparent solar cells exhibit average photopic-response-weighted transmittances of 80.3−82.0% and color-rendering indices of 95.0−97.1, both of which are records for organic photovoltaics, with power-conversion efficiencies of 0.43−0.70%.</